2018
DOI: 10.12659/msm.912142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TurboHawk Plaque Rotation System in Treatment of Superficial Femoral Atherosclerosis

Abstract: BackgroundTo investigate the curative effect and utility of the TurboHawk plaque circumcision system in the treatment of patients with superficial femoral atherosclerosis (SFA).Material/MethodsWe retrospectively analyzed 60 cases of superficial femoral atherosclerotic stenosis and occlusion treated with the TurboHawk plaque circumcision system for endovascular ablation of the superficial femoral artery in the People’s Hospital of Xinjiang Uygur Autonomous Region between January 2016 and December 2017.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…[ 1 , 2 , 5 , 6 ] Previous similar studies suggested THPRS for the treatment of patients with AOLE. [ 27 , 28 ] One study reported THPRS in the treatment of patients with superficial femoral atherosclerosis (SFA). [ 27 ] It retrospectively analyzed 60 patient case records (including 50 males and 10 females) of superficial femoral atherosclerotic stenosis and occlusion treated by THPRS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 1 , 2 , 5 , 6 ] Previous similar studies suggested THPRS for the treatment of patients with AOLE. [ 27 , 28 ] One study reported THPRS in the treatment of patients with superficial femoral atherosclerosis (SFA). [ 27 ] It retrospectively analyzed 60 patient case records (including 50 males and 10 females) of superficial femoral atherosclerotic stenosis and occlusion treated by THPRS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 , 28 ] One study reported THPRS in the treatment of patients with superficial femoral atherosclerosis (SFA). [ 27 ] It retrospectively analyzed 60 patient case records (including 50 males and 10 females) of superficial femoral atherosclerotic stenosis and occlusion treated by THPRS. [ 27 ] Its findings showed that THPRS may be effective for the management of SFA in a short period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations